Small intestinal submucosa-derived extracellular matrix as a heterotopic scaffold for cardiovascular applications - Palmosi, Tiziana; Tolomeo, Anna Maria; Cirillo, Carmine; Sandrin, Debora; Sciro, Manuela; Negrisolo, Susanna; Todesco, Martina; Caicci, Federico; Santoro, Michele; Dal Lago, Eleonora; Marchesan, Massimo; Modesti, Michele; et al. (Frontiers in Bioengineering and Biotechnology, 2022)
Structural cardiac lesions are often surgically repaired using prosthetic patches, which can be biological or synthetic. Amongst biological patches, in the current clinical scenario, those derived from the decellularization of the xenogeneic scaffold are gaining more interest, as they maintain their natural architecture of the extracellular matrix (ECM) after the removal of their native cells and their remnants. Once implanted in the host, they can induce tissue regeneration and repair, encouraging angiogenesis, migration, proliferation, and host cell differentiation. Lastly, decellularized xenogeneic patches undergo cell repopulation thus reducing host immuno-mediated response against the graft and preventing device failure. Porcine Small Intestinal Submucosa (SIS) has shown such properties in alternative clinical scenarios. Specifically, the US FDA has approved its use in humans for urogenital procedures, such as hernia repair, cystoplasties, ureteral reconstructions, stress incontinence, Peyronie’s disease, penile chordee, and even urethral reconstruction for hypospadias and strictures. In addition, it has also been successfully used for skeletal muscle tissue reconstruction in young patients, but for cardiovascular applications, the results are controversial of this study. With this study, we aimed to validate our decellularization protocols for SIS, which is based on the use of Tergitol 15 S 9, by comparing it to our previous and efficient method (Triton X 100), not available on the market. For both treatments, we evaluated the preservation of the ECM ultrastructure, biomechanical features, biocompatibility, and final bioinductive capabilities. The overall analysis shows that the SIS tissue is macroscopically distinguishable into two regions, one smooth and one wrinkle equivalent for ultrastructure, biochemical and proteomic profile. Furthermore, Tergitol 15 S 9 treatment does not modify tissue biomechanics, resulting in comparable to the native one and confirming the superior preservation of the collagen fibers. In summary, the present study showed that the SIS decellularized with Tergitol 15 S 9 guarantees higher performances compared to the Triton X 100 method in all the fields of characterization explored and for all the components of the SIS, rough and smooth.